The prognostic value of the combination of body composition and systemic inflammation in patients with cancer cachexia. Issue 2 (5th March 2023) - Xie, Hai‐Lun; Ruan, Guo‐Tian; Wei, Lishuang; Zhang, Qi; Ge, Yi‐Zhong; Song, Meng‐Meng; Zhang, Xi; Lin, Shi‐qi; Liu, Xiao‐yue; Zhang, Xiao‐Wei; Li, Xiang‐Rui; Zhang, Kang‐Ping; et al.
Abstract: Background: Changes in body composition and systemic inflammation are important characteristics of cancer cachexia. This multi‐centre retrospective study aimed to explore the prognostic value of the combination of body composition and systemic inflammation in patients with cancer cachexia. Methods: The modified advanced lung cancer inflammation index (mALI), which combines body composition and systemic inflammation, was defined as appendicular skeletal muscle index (ASMI) × serum albumin/neutrophil‐lymphocyte ratio. The ASMI was estimated according to a previously validated anthropometric equation. Restricted cubic splines were used to evaluate the relationship between mALI and all‐cause mortality in patients with cancer cachexia. Kaplan–Meier analysis and Cox proportional hazard regression analysis were used to evaluate the prognostic value of mALI in cancer cachexia. A receiver operator characteristic curve was used to compare the effectiveness of mALI and nutritional inflammatory indicators in predicting all‐cause mortality in patients with cancer cachexia. Results: A total of 2438 patients with cancer cachexia were enrolled, including 1431 males and 1007 females. The sex‐specific optimal cut‐off values of mALI for males and females were 7.12 and 6.52, respectively. There was a non‐linear relationship between mALI and all‐cause mortality in patients with cancer cachexia. Low mALI was significantly associated with poor nutritional status, high tumour burden, and high inflammation. Patients with low mALI had significantly lower overall survival (OS) than those with high mALI (39.5% vs. 65.5%, P  < 0.001). In the male population, OS was significantly lower in the low mALI group than in the high group (34.3% vs. 59.2%, P  < 0.001). Similar results were also observed in the female population (46.3% vs. 75.0%, P  < 0.001). mALI was an independent prognostic factor for patients with cancer cachexia (hazard ratio [HR] = 0.974, 95% confidence interval [CI] = 0.959–0.990, P  = 0.001). For every standard deviation [SD] increase in mALI, the risk of poor prognosis for patients with cancer cachexia was reduced by 2.9% (HR = 0.971, 95%CI = 0.943–0.964, P  < 0.001) in males and 8.9% (HR = 0.911, 95%CI = 0.893–0.930, P  < 0.001) in females. mALI is an effective complement to the traditional Tumour, Lymph Nodes, Metastasis (TNM) staging system for prognosis evaluation and a promising nutritional inflammatory indicator with a better prognostic effect than the most commonly used clinical nutritional inflammatory indicators. Conclusions: Low mALI is associated with poor survival in both male and female patients with cancer cachexia and is a practical and valuable prognostic assessment tool.